Increasing Amino Acids Density Improves Broiler Live Weight - Nasr, J.; Kheiri, F. (International Journal of Poultry Science, 2011)
This research evaluates amino acid density in two phases throughout life in Arian male broilers to better understand the impact of increase and decrease dietary amino acids density in live weight performance. Four diets with different levels of amino acids density, High (H), Medium (M), Standard (S) and Low (L) were used in a completely randomized experimental design. All diets were isocaloric and isonitrogenous. Broilers fed H diet, body weight in 42 d was increased by 202 g compared with standard group (p